Imagining communities with ‘intelligent’ machines - Katja Valaskivi (Journal of Digital Social Research)
Shared perceptions of the world are imagined with and within available media technological environments. In other words our communication environment conditions our social imagination and the ways in which we can see the world. The essay, based on the inaugural lecture of the author, discusses how this conditioning takes place and with what consequences in the contemporary digital societies. The essay draws on the research by the author on innovationism and discusses the concepts of reversed tools, content confusion and attention factory. Utilizing the study by Berg & Valaskivi (2023) on commercial image recognition services and their performance in recognizing religion in images as an example, the essay illustrates failures and imperfections of AI technologies which are often considered more neutral than human beings. The essay calls for critical thinking on digitalization and expansion of AI technologies and encourages prioritization of humane interests as well as social and cultural welbeing over commerciality in technological development.